Effectiveness Test of Botanical Pesticide Formulation of Combination of Lime Leaves and Lemongrass Against Aphids (Aphis spp.) on Katokkon Chili Plants in-Vitro - Driyunitha; Yulius Pakiding; Sion Oktafianus (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Aphids (Aphis spp.) are one of the main pests that damage Katokkon chilies by sucking plant sap and transmitting viruses. Excessive use of chemical pesticides can lead to resistance and environmental problems; therefore, environmentally friendly alternatives are needed. This study aims to determine the effectiveness of a botanical pesticide formulation derived from lime (Citrus spp.) leaves and citronella (Cymbopogon nardus) against Aphis spp. Mortality in vitro. This experiment used a completely randomized design with 7 treatment levels (R1-R5, KP, KN) and 5 replications. Observed parameters included physicochemical stability of the formulation (pH, density and viscosity), pest mortality from 4-72 hours and toxicity based on probit analysis (LT50). Results showed that formulations were stable in storage for 14 days, with the smallest changes in pH, density and viscosity. The highest mortality was found in R4 (83.33%), followed by R3 (70.83%) and R2 (62.50%), while solvent control reached only 2.50%. Probit analysis revealed that R4 gave the shortest LT50 value (8.70 hours), followed by R3 (24.93 hours) and R2 (35.61 hours). Based on these results, a combination of lime and citronella, with a ratio of 25%:75% (R4), is the most effective formulation as a botanical pesticide against Aphis spp.